Membangun Kesadaran Stunting pada Masyarakat Desa Gedongjetis, Kecamatan Tulung, Kabupaten Klaten - Amrullah, M. Fikri; Alam, Achmad Farhan Fauzan; Rizkha, Syafitri Cintia Nur (Universitas Negeri Semarang, 2024)
This article discusses the community service activities carried out by the KKN UNNES GIAT 7 team in an effort to increase public awareness of stunting. Stunting is still prevalent in Indonesia and requires swift and precise handling. The article outlines the objectives of this effort, namely to raise public awareness, encourage prompt and appropriate action, integrate an understanding of stunting into daily life, initiate a grassroots approach, and develop a healthy and quality generation. The benefits of this effort include improved health and welfare of the community, increased productivity and competitiveness, quality human development, social and economic improvement, and the formation of a health-conscious society. Implementation methods include initial observation, a 3-day activity implementation, and final outcome evaluation. With this approach, public awareness of stunting is hoped to increase and preventive measures can be carried out more effectively.